The Effect of Substrate Concentration on Enzymatic Hydrolysis of Selected Food Waste for Glucose Production - Micky, Vincent (Hibiscus Publisher, 2015)
Food waste from households and restaurants is a major component of municipal solid waste [1]. In a recent study by Pleisser and Lin [2], it was reported that approximately 1.3 billion tonnes of untreated food waste is deposited at numerous landfill sites. Based on the current (2014) estimates, approximately 100 million tons of food are wasted annually in the eu alone, and this is expected to rise to about 126 million tonnes by the year 2020 [3].